2020
DOI: 10.1038/s41467-020-16374-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of primitive methane-cycling ecosystems and early Earth’s atmosphere and climate

Abstract: The history of the Earth has been marked by major ecological transitions, driven by metabolic innovation, that radically reshaped the composition of the oceans and atmosphere. The nature and magnitude of the earliest transitions, hundreds of million years before photosynthesis evolved, remain poorly understood. Using a novel ecosystem-planetary model, we find that pre-photosynthetic methane-cycling microbial ecosystems are much less productive than previously thought. In spite of their low productivity, the ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…A widespread occurrence of AOM coupled to Fe oxidation offers an alternative explanation that would have led to the decrease of dissolved CH 4 in the ocean and consequently the emission of CH 4 to the atmosphere, thus going in the direction of the study of Riedinger et al 39 . This is consistent with the revision of the putative composition of the Archean atmosphere 55 that suggests that the amount of greenhouse warming by CH 4 was more limited than previously thought 49 , 56 .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A widespread occurrence of AOM coupled to Fe oxidation offers an alternative explanation that would have led to the decrease of dissolved CH 4 in the ocean and consequently the emission of CH 4 to the atmosphere, thus going in the direction of the study of Riedinger et al 39 . This is consistent with the revision of the putative composition of the Archean atmosphere 55 that suggests that the amount of greenhouse warming by CH 4 was more limited than previously thought 49 , 56 .…”
Section: Resultssupporting
confidence: 90%
“…However, geological archives do not provide constraints on the magnitude of the CH 4 concentrations, and large CH 4 fluxes are calculated with quantitative models that limit the existence of Fe-dependent CH 4 oxidation and assume a negligible role of SO 4 2− driven CH 4 oxidizers. This paradigm has recently been challenged by Olson et al 48 and Sauterey et al 49 who showed that the combined effects of competition between methanogens and SO 4 2− reducers and occurrence of SO 4 2− driven CH 4 oxidation would have effectively reduced the CH 4 fluxes from the ocean even at modest SO 4 2− concentrations, and regardless of O 2 concentrations. Similarly, we propose that strong interactions between photoferrotrophs and Fe-dependent CH 4 oxidizers might have exerted an important control on the Archean–Proterozoic CH 4 cycling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Or, conversely, given that the early Earth was not frozen, if the rest of the climate system had remained unaltered then the oceans would now be boiling under today's brighter Sun. Evidently neither occurred, for reasons that are still debated [8][9][10][11][12] ; although plausible solutions exist, in particular when combining multiple processes 13 , as yet there is no firm consensus as to how in reality the 'Faint Young Sun Paradox' was overcome 14 .…”
mentioning
confidence: 99%